2015
DOI: 10.1371/journal.pone.0138626
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that the Malaria Parasite Plasmodium falciparum Putative Rhoptry Protein 2 Localizes to the Golgi Apparatus throughout the Erythrocytic Cycle

Abstract: Invasion of a red blood cell by Plasmodium falciparum merozoites is an essential step in the malaria lifecycle. Several of the proteins involved in this process are stored in the apical complex of the merozoite, a structure containing secretory organelles that are released at specific times during invasion. The molecular players involved in erythrocyte invasion thus represent potential key targets for both therapeutic and vaccine-based strategies to block parasite development. In our quest to identify and char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Our attempts at knockdown of PfFH levels by removal of trimethoprim from cultures of FH-RFA expressing strain, where FH is fused to EcDHFR degradation domain, did not result in lowering of protein levels. It has been shown that proteins targeted to organelles and possessing a signal sequence lack accessibility to proteasomal degradation machinery and hence the conditional degradation approach may be unsuitable for achieving knockdown of these protein levels (36). Therefore, the essentiality of FH was examined in P. berghei with BALB/c mice as host.…”
Section: Essentiality Of Fumarate Hydratase For Pmentioning
confidence: 99%
“…Our attempts at knockdown of PfFH levels by removal of trimethoprim from cultures of FH-RFA expressing strain, where FH is fused to EcDHFR degradation domain, did not result in lowering of protein levels. It has been shown that proteins targeted to organelles and possessing a signal sequence lack accessibility to proteasomal degradation machinery and hence the conditional degradation approach may be unsuitable for achieving knockdown of these protein levels (36). Therefore, the essentiality of FH was examined in P. berghei with BALB/c mice as host.…”
Section: Essentiality Of Fumarate Hydratase For Pmentioning
confidence: 99%
“…We had previously unsuccessfully tried to conditionally regulate the expression of GP1 by using the DHFR destabilisation domain (Muralidharan, Oksman, Iwamoto, Wandless, & Goldberg, 2011, Hallee & Richard, 2015 so we decided to switch to the glmS ribozyme system and generated a marker-free GP1-3HA-glmS tagged line by using the CRISPR-Cas9 technology ( Figure S5A; Ghorbal et al, 2014, Theriault & Richard, 2017. Proper integration of the 3HA-glmS cassette at the 3′ end of the GP1 gene was verified by Southern blot and PCR before and after parasite cloning ( Figure S5B-C).…”
Section: Knockdown Of Gp1 Affects In Vitro P Falciparum Asexual Stmentioning
confidence: 99%
“…Our previous work determined that the P. falciparum Putative Rhoptry Protein 2 (PRP2, PF3D7_1320000) resided in the Golgi and not in the rhoptries, which led us to rename it Golgi Protein 1 (GP1; Tufet‐Bayona et al, , Hallee & Richard, ). We show here that GP1 interacts with a unique and previously uncharacterised transmembrane protein (PF3D7_1123500), which we have named Golgi Protein 2 (GP2).…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescence microscopy acquisition was performed as previously described (Hallee & Richard, ; Counihan et al, ) and using a GE Applied Precision Deltavision Elite microscope and an Olympus IX71 microscope with 100 × 1.4NA objective and with a sCMOS camera and deconvolved with the SoftWorx software. For immunofluorecence assays, parasites were fixed with cold MeOH (Dietz et al, ), cold 90% acetone/10% MeOH, or 4% paraformaldehyde (ProSciTech).…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence microscopy acquisition was performed as previously described (Hallee & Richard, 2015;Counihan et al, 2017)…”
Section: Microscopymentioning
confidence: 99%